KOMPUTASI NUMERIK GERAK PROYEKTIL DUA DIMENSI MEMPERHITUNGKAN GAYA HAMBATAN UDARA DENGAN METODE RUNGE-KUTTA4 DAN DIVISUALISASIKAN DI GUI MATLAB - Tatik Juwariyah (Bina Teknika, 2015)
The simulation of two dimensional projectile motion problem with including resisting force as velocity function in MATLAB program has been done.The two dimensional projectile motion problem was formulated in second order differential equation which included resitance form as linier velocity function. The second order differential of motion then separated into two coupled first order differential equation and then numerically was soluted by Runge_Kutta4 method. The visualisation of computation values as a path of projectile motion and others physics quantities like dissipation energy were shown by MATLAB GUIDE.